Pattern of Diet Consumption and Levels of Knowledge Regarding Diabetes among Diabetic Adults Belongs to Rural and Urban Community Areas, Uttarakhand: A Cross-sectional Comparative Survey - Vasantha C. Kalyani; Sonia; Neetu Kataria; Kusum Kumari (Journal of Applied Sciences and Clinical Practice)
Background: The prevalence of diabetes is among the highest in the world and comparable to that of West Asia and the Pacific. This study aims to determine the pattern of diet consumption and levels of knowledge regarding diabetes among diabetic adults belongs to rural and urban community areas, Uttarakhand: A cross-sectional comparative survey. Materials and Methods: A cross-sectional comparative survey was conducted upon 161 human diabetic adults selected from rural and urban communities, Uttarakhand. Outcomes were knowledge regarding diabetes, diet consumption, and mean difference between knowledge questionnaires and their comparison among urban and rural communities. Results: The mean age and RBS of the participants were 36.8 ± 1.2 years and 113.8 ± 46.5 mg/dL. The knowledge regarding diabetes and treatment strategies was poor among all participants. The average days of consumption of diet were 2.6 days in a week which is quiet low for respective food items listed above. It can be interpretated that fruits consumption in diet directly affected by knowledge regarding diabetes among adults with diabetes. Finally, no difference found in pattern of diet consumption and knowledge related diabetes between the urban and rural communities. Conclusion: The study concluded that the knowledge regarding diabetes was poor among all participants. The average days of consumption of diet in terms of recommended dietary allowances were 2–3 days in a week which was quiet average. The consumption of fruits in diet was directly affected by knowledge regarding diabetes among adults with diabetes.